2020
DOI: 10.3390/ijerph17249495
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Assessment Tool (BAT)—Development, Validity, and Reliability

Abstract: This paper introduces a new definition for burnout and investigates the psychometric properties of the Burnout Assessment Tool (BAT). In a prior qualitative study, 49 practitioners were interviewed about their conceptualization of burnout (part 1). Using a dialectical approach, four core dimensions—exhaustion, mental distance, and impaired emotional and cognitive impairment—and three secondary dimensions—depressed mood, psychological distress, and psychosomatic complaints—emerged, which constitute the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
684
2
40

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 401 publications
(769 citation statements)
references
References 67 publications
43
684
2
40
Order By: Relevance
“…Results of the CFA indicated that model fit the data very well both in the sample at Time 1 (N = 590; X 2 = 1593.171, df = 512; SRMR = 0.057; CFI = 0.91; RMSEA = 0.06) and in the two-wave sample at T2 (N = 190; X 2 = 1048.150, df = 512; SRMR = 0.062; CFI = 0.89; RMSEA = 0.07). For completeness, we also tested the second-order model of burnout on the sample at T1 and results are consistent to Schaufeli et al (2020) showing that the fit of the model was adequate (N = 590; X 2 = 1828.559, df = 521; SRMR = 0.072; CFI = 0.89; RMSEA = 0.06), although it was slightly worse than the six-factor correlated model. models are not accepted (Hooper et al, 2008).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Results of the CFA indicated that model fit the data very well both in the sample at Time 1 (N = 590; X 2 = 1593.171, df = 512; SRMR = 0.057; CFI = 0.91; RMSEA = 0.06) and in the two-wave sample at T2 (N = 190; X 2 = 1048.150, df = 512; SRMR = 0.062; CFI = 0.89; RMSEA = 0.07). For completeness, we also tested the second-order model of burnout on the sample at T1 and results are consistent to Schaufeli et al (2020) showing that the fit of the model was adequate (N = 590; X 2 = 1828.559, df = 521; SRMR = 0.072; CFI = 0.89; RMSEA = 0.06), although it was slightly worse than the six-factor correlated model. models are not accepted (Hooper et al, 2008).…”
Section: Discussionsupporting
confidence: 64%
“…Burnout was measured using the BAT (BAT, Schaufeli et al, 2020 ) Italian version adapted by Consiglio et al (unpublished) 2 . The 34 BAT items are distributed along six sub-dimensions that include the four core (four subscales) and secondary (two subscales) symptoms of burnout with the following items’ distribution: (1) exhaustion, eight items (item example: “When I get up in the morning, I lack the energy to start a new day at work”); (2) mental distance, five items (item example: “I feel indifferent about my job”); (3) emotional impairment, five items (item example “At work, I may overreact unintentionally”); (4) cognitive impairment, five items (item example: “At work, I struggle to think clearly”); (5) psychosomatic complaints, five items (item example “I suffer from palpitations or chest pain”); and (6) psychological distress, six items (item example “I have trouble falling or staying asleep.” Items were assessed on a 5-point Likert scale ranging from 1 “never” to 5 “always.”…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations